Antiresorptive effect of a cathepsin K inhibitor ONO-5334 and its relationship to BMD increase in a phase II trial for postmenopausal osteoporosis - Makoto Tanaka; Yoshitaka Hashimoto; Chihiro Hasegawa; Steve Deacon; Richard Eastell (BMC Musculoskeletal Disorders, 2017)
Abstract Background ONO-5334 is a cathepsin K inhibitor that induced bone mineral density (BMD) gain in a phase II study in postmenopausal osteoporosis patients. Even though the antiresorptive effect could only be monitored in the morning during the study, simulation can allow the antiresorptive effect to be assessed over 24 h, with assessment of the relationship to BMD gain. Methods Inhibition of the serum C-telopeptide of type I collagen (sCTX) level at doses of ONO-5334 of 100 mg once daily (QD), 300 mg QD, and 50 mg twice daily (BID) was simulated using plasma ONO-5334 pharmacokinetic (PK) data for repeated dose administration in a phase I study and corresponding sCTX inhibition from the PK-pharmacodynamic (PK/PD) relationship. sCTX was selected because it has a high signal-to-noise ratio compared to other telopeptides. A negative sigmoidal shape for the PK/PD relationship between plasma ONO-5334 and sCTX levels was obtained in our previous study. Results The simulated sCTX inhibition reached >99% of the maximal inhibitory effect (Emax) at 0.5 h in all treatment groups, and decreased to <80% Emax at 8 and 12 h at 50 mg BID and 100 mg QD, respectively. However, sCTX inhibition at 300 mg QD was maintained at ≥82% Emax over 24 h. The mean sCTX inhibition rates for 24 h at 100 mg QD, 300 mg QD and 50 mg BID were 63, 95 and 80% Emax, respectively. There was a positive linear relationship by treatment group between mean sCTX inhibition over 24 h and observed BMD gain in the phase II study. Conclusion The dose response for BMD with ONO-5334 at 100 and 300 mg QD and higher BMD gain at 50 mg BID vs. 100 mg QD can be explained by sCTX inhibition over 24 h. The simulation gave the antiresorptive effect of ONO-5334 over 24 h and allowed prediction of BMD gain due to ONO-5334. Trial registration The registration number in The European Union Clinical Trials Register is 2007–002417-39 . The date of registration was August 31, 2007.